The innovator's hypothesis : how cheap experiments are worth more than good ideas - Schrage, Michael (The MIT Press, 2014)
In this book Michael Schrage advocates a cultural and strategic shift: small teams, collaboratively--and competitively--crafting business experiments that make top management sit up and take notice. Creativity within constraints--clear deadlines and clear deliverables--is what serious innovation cultures do. He introduces the 5X5 framework: giving diverse teams of five people up to five days to come up with portfolios of five business experiments costing no more than $5,000 each and taking no longer than five weeks to run. The book describes multiple portfolios of 5X5 experiments drawn from Schrage's advisory work and innovation workshops worldwide. -- Edited summary from book.
Keywords: Technological innovations.; Creative ability in business.; elektronické knihy; electronic books